‘Progressive’, ‘fantastical’, and/or ‘postmodern’? Italo Calvino in Estonian Culture from the Post-War to the New Millennium - Monticelli, Daniele; Kristiina Rebane (Incontri. Rivista europea di studi italiani, 2025)
Italo Calvino in Estonian Culture from the Post-War to the New Millennium This article reconstructs Italo Calvino’s reception in Estonia, focusing on its interaction with the country’s literary, cultural, and political history. The analysis reveals that this interaction cannot be strictly deterministic. Radical changes in Estonia’s political and cultural context since World War II influenced Calvino’s translation and reception, yet other dynamics also played a role. In Soviet Estonia, initial interest in Calvino stemmed from his Communist Party affiliation. His neorealist works, reflecting his political militancy, were first translated in the Soviet Union in the 1950s. Interest in neorealist Calvino waned soon after in Soviet Estonia. By the 1960s, attention shifted to his fantastical, allegorical, and ironic works like Our Ancestors and Marcovaldo, with a focus on his reflections on the relationship between intellectuals, politics, and society. After Estonia’s independence in 1991, the shift to a capitalist market economy increased the quantity and diversity of published books but decreased print runs and interest in foreign literature. Postmodernist works like Palomar and If on a winter’s night a traveler received lukewarm responses, while Invisible Cities and Six Memos for the Next Millennium became cult texts for a small group of intellectuals, as evidenced by the frequent mentions of these works in Estonian cultural periodicals. However, his popularity among the larger public peaked during the Soviet era and has since declined, leading publishers to be reluctant to release new Calvino texts.